P149 The intracellular chloride channel 4 (CLIC4) plays an important role in systemic sclerosis fibroblast activation. (26th April 2021) - Wasson, Christopher; Ross, Rebecca; Morton, Ruth; Mankouri, Jamel; Del Galdo, Francesco
Abstract: Background/Aims   The intracellular chloride ion channel CLIC4 mediates the activation of cancer associated fibroblasts. Interestingly, systemic sclerosis (SSc) fibroblasts display a number of similar properties to cancer associated fibroblasts. Tissue fibrosis in SSc is driven by active fibroblasts (myofibroblasts). Therefore in this study we investigated the role of CLIC4 in SSc fibroblast activation. Methods   Dermal fibroblasts were obtained from full thickness skin biopsies from SSc patients (early-diffuse). RNA and protein were collected from the fibroblasts and CLIC4 transcript and protein levels were assessed by qPCR and western blot. SSc patient fibroblasts were treated with the chloride ion channel inhibitors NPPB and IAA-94. Results   CLIC4 was found to be expressed at significantly higher levels in SSc patients fibroblasts compared to healthy controls, at both the transcript (3.7 fold) and protein (1.7 fold) levels. Inhibition of the TGF-β signalling pathway led to reduced CLIC4 expression in SSc fibroblasts, confirming this pathway as the main driver of CLIC4 expression. Finally, treatment of SSc fibroblasts with small molecule inhibitors that target the channel led to reduced expression of the myofibroblast markers collagen type 1 and alpha-smooth muscle actin, suggesting a direct role for CLIC4 in SSc associated skin fibrosis. Conclusion   We have identified a novel role for CLIC4 in SSc myofibroblast activation, which further strengthen the similarities between SSc fibroblasts and cancer associated fibroblasts. Furthermore this study highlights this channel as a novel target for therapeutic intervention. Disclosure   C. Wasson: None. R. Ross: None. R. Morton: None. J. Mankouri: None. F. Del Galdo: None.